THE EFFECT OF DIMETHYL ETHER (DME) AS LPG SUBSTITUTION ON HOUSEHOLD STOVE: MIXTURE STABILITY, STOVE EFFICIENCY, FUEL CONSUMPTION, AND MATERIALS TESTING - Murti, Galuh Wirama; Priyanto, Unggul; Masfuri, Imron; Adelia, Nesha (Deputi TIRBR-BPPT, 2021)
DME has characteristics similar to LPG so that the storage and handling are not so different from LPG. DME could be used as a solvent that can extract typical types of rubber/polymer material. The aims and objectives of this study are to determine the effect of DME/LPG (100/0, 80/20, 50/50, 30/70, 20/80) on the stability of the DME/LPG mixture on the stove and also to observe the effect on several rubber materials/polymers on stove accessories. The study reveals that the usage of a DME/LPG mixture between 20/80 - 30/70 does not require a replacement of any substitute materials but only requires minor modifications to the stove. However, at a higher DME composition, the use of the fuel needs to replace the seal that is resistant to DME. It occurs due to the change of the gas composition when it is used.